A Simple Method for Preparing Carbon‐doped CoP to Enhance Hydrogen Evolution Reaction. Issue 28 (26th July 2021) - Yuan, Guojun; Bai, Jianliang; Zhang, Lu; Wang, Xinyu; Zhu, Yaqing; Wu, Shuang; Ren, Lili
Abstract: Exploring low cost, highly active catalysts toward electrocatalytic hydrogen evolution reaction has become a research hotspot for researchers. In this regard, the precursor of CoP was obtained by hydrothermal method, and CoP was obtained by phosphating after treatment in different atmospheres. Among them, the final sample obtained by nitrogen treatment is CoP/C. The carbon doping structure can promote electron transfer from CoP and improve the performance of the electrolytic water hydrogen evolution reaction. The results show that the HER properties of the samples with carbon‐doped structure prepared at 120 °C and 150 °C in 0.5 M H2 SO4 solution are significantly better than those of the samples without such structure. Meanwhile, CoP/C‐120 has a relatively lower overpotential (286 mV at 10 mA cm −2 ) and good stability in 100000 s. And the reason of the high activity of this catalyst was also discussed through TEM and XPS characterization. The present study provides a promising avenue toward the design of carbon atom doped catalysts. Abstract : By calcining the precursor for preparing CoP in nitrogen atmosphere, the sample containing carbon doping structure was obtained. The existence of this special structure is conducive to the dispersion of CoP and the rapid transfer of electrons in it, which plays a certain role in the effective improvement of HER performance of CoP.